Portrayal of Men and Women in English and Palestinian Arabic Proverbs: (Focus on Negative Attributes) - Yusra Shadeed; Prof. Aziz Khalil (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
Proverbs reflect unique beliefs, values and experiences of cultures and societies. This study was mainly undertaken to investigate the representation of men and women in English and Palestinian Arabic proverbs, focusing on negative attributes. The study employed a qualitative approach, and the sample consisted of English and Palestinian Arabic proverbs that mention men or women explicitly or implicitly. All proverbs were collected from various resources including books, dictionaries and online sites. Proverbs were thematically categorized focusing on the meaning of these proverbs and the negative personal attributes reflected by them. This study adopted Fairclough's (1989) three-dimensional model to analyze English and Palestinian Arabic proverbs. Finally, the researchers contrasted the representation of men and women in English and Palestinian Arabic proverbs to identify any aspects of imbalance and bias in the portrayal of men and women in the selected proverbs. This study revealed similarities between English and Palestinian Arabic proverbs despite the many differences in both societies in terms of their cultures, language, religion, history, family structures, social standards, and geographical locations. The researchers recommend that further research be conducted into how women and men are portrayed in proverbs from around the world to reinforce the findings reached in the present study.